2013
DOI: 10.1177/0969141313485729
|View full text |Cite
|
Sign up to set email alerts
|

Screening for prostate cancer in New Zealand general practice

Abstract: Objective To ascertain the rates and patterns of prostate-specific antigen (PSA) screening in New Zealand men. Methods The study population included 35,958 men aged 40þ years, with no prior diagnosis of prostate cancer, enrolled in 31 general practices in the Midland Cancer Network Region of New Zealand in 2010. Computerized practice records were searched for information, including reasons for testing, for men with elevated PSA test results in 2010. PSA results for 2007-2010 were obtained from community labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Similar to the findings of others, PSA testing rates increase with age, 14–16 18–20 and peak testing prevalence is among the patients aged 70–80 years old. 14 15 18–20 A third of those aged ≥70 years have PSA levels ≥4 ng/mL, 14 15 21 which was consistent with our own findings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to the findings of others, PSA testing rates increase with age, 14–16 18–20 and peak testing prevalence is among the patients aged 70–80 years old. 14 15 18–20 A third of those aged ≥70 years have PSA levels ≥4 ng/mL, 14 15 21 which was consistent with our own findings.…”
Section: Discussionsupporting
confidence: 88%
“…We observed a significant degree of variability in the PSA testing rate between practices, which is similar to previous findings, IQR 3.6–8.4% (Williams et al 15 ), and may be a reflection of differences in practice organisation, GP attitudes to testing or patient demographics. Yearly PSA testing rates also vary greatly between developed countries with greater testing in some EU countries (Germany 35%), 16 New Zealand (22%) 18 and a greater degree of testing in the USA (57%). 19 Hjertholm et al 13 found no difference in prostate cancer-specific mortality between Danish practices with the highest and lowest relative levels of PSA testing, but there was a significant increase in prostate cancer diagnoses (mainly local disease), prostate biopsy and prostatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a community survey by the Prostate Cancer Foundation of Australia in 2013 reported that 6% of respondents aged 18–24 had undergone at least one test for prostate cancer . A large general‐practice‐based study in New Zealand in 2010 suggested an overall screening rate of 22% of the 35 958 men aged ≥40 years of age, with PSA screening in 24% of men aged ≥70 years . These data show significant rates of screening, including in the very young and very old, populations that were not included in studies and that are not advocated for screening in any of the current recommendations.…”
Section: Population Screeningmentioning
confidence: 94%
“…Although screening for prostate cancer is not recommended in New Zealand due to the controversy about its harms versus benefits [ 5 – 7 ], it is common in New Zealand general practice [ 8 , 9 ]. Screening rates in New Zealand are similar to other countries with privatised primary care services, such as the USA, Canada and Australia [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%